National- to port-level inventories of shipping emissions in China. (7th November 2017) - Fu, Mingliang; Liu, Huan; Jin, Xinxin; He, Kebin
Abstract: Shipping in China plays a global role, and has led worldwide maritime transportation for the last decade. However, without taking national or local port boundaries into account, it is impossible to determine the responsibility that each local authority has on emission controls, nor compare them with land-based emissions to determine the priority for controlling these emissions. In this study, we provide national- to port-level inventories for China. The results show that in 2013, the total emissions of CO, non-methane volatile organic compounds (NMVOCs), nitrogen oxides (NO x ), particulate matter (PM), SO2 and CO2 were 0.0741 ± 0.0004 Tg∙yr −1, 0.0691 ± 0.0004 Tg∙yr −1, 1.91 ± 0.01 Tg∙yr −1, 0.164 ± 0.001 Tg∙yr −1, 1.30 ± 0.01 Tg∙yr −1 and 86.3 ± 0.3 Tg∙yr −1 in China, respectively. By providing high-resolution spatial distribution maps of these emissions, we identify three hotspots, centered on the Bohai Rim Area, the Yangtze River Delta and Pearl River Delta. These three hotspots account for 8% of the ocean area evaluated in this study, but contribute around 37% of total shipping emissions. Compared with on-road mobile source emissions, NO x and PM emissions from ships are equivalent to about 34% and 29% of the total mobile vehicle emissions in China. Moreover, this study provides detailed emission inventories for 24 ports in the country, which also greatly contributes to our understanding of global shipping emissions, given that eight of these ports rank within the top twenty of the port league table. Several ports in China suffer emissions 12–147 times higher than those at Los Angeles port. The ports of Ningbo-Zhou Shan, Shanghai, Hong Kong and Dalian dominate the port-level inventories, with individual emissions accounting for 28%–31%, 10%–14%, 10%–12% and 8%–14% of total emissions, respectively.